Tryptophan Hydroxylase 2 Genotype Determines Brain Serotonin Synthesis but Not Tissue Content in C57Bl/6 and BALB/c Congenic Mice - Siesser, William B. (2010)
Tryptophan hydroxylase 2 (TPH2) catalyzes the rate-limiting step in the synthesis of brain serotonin (5-HT). In a previous report, a single nucleotide polymorphism in mTph2 (C1473G) reduced 5-HT synthesis by 55%. Mouse strains expressing the 1473C allele, such as C57Bl/6, have higher 5-HT synthesis rates than strains expressing the 1473G allele, such as BALB/c. Many studies have attributed strain differences to Tph2 genotype without ruling out the potential role of alterations in other genes. To test the role of the C1473G polymorphism in strain differences, we generated C57Bl/6 and BALB/c mice congenic for the Tph2 locus. We found that the 1473G allele reduced 5-HT synthesis in C57Bl/6 mice but had no effect on 5-HT tissue content except for a slight reduction (15%) in the frontal cortex. In BALB/c mice, the 1473C allele increased 5-HT synthesis but again did not affect 5-HT tissue content. At the same time, 5-hydroxyindoleacetic acid (5-HIAA) was significantly elevated in BALB/c congenic mice. In C57Bl/6 mice, there was no effect of genotype on 5-HIAA levels. BALB/c mice had lower expression of monoamine oxidase A and B than C57Bl/6 mice, but there was no effect of Tph2 genotype. On the tail suspension test, escitalopram treatment reduced immobility regardless of genotype. These data demonstrate that the C1473G polymorphism determines differences in 5-HT synthesis rates among strains but only minimally affects 5-HT tissue levels.